(3JNQjL CMGOjK Gdhbas - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s
(3ChdgG (B:s
(3GdQMef eJQhc hCNQL GdHjgbj aj GdTYH Yf eMeO Hf gQhf GdaCaGA hcGf KbI UOhbG bGd QCjJ GdfHj Udi Gddg Ydjg hSde GdefGe abdJ jG QShd Gddg (B, (3MOjK Ydj Hf YGUes
(3BNQgG (B:s
(3bOQ PGJ gLQ hGfaGO hef cGf CMX YXje jScf Edi NHGH GdYdi GdbOS JMOh Hg GdYGOjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 301s
(3eYLe GdeDdajf (B2 / 82s
(3TPQGJ GdPgH (B8 / 51s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdMOjK hGdeUWdMs